The impact of cigarette branding and plain packaging on perceptions of product appeal and risk among young adults in Norway: A between-subjects experimental survey. Issue 12 (4th December 2013) - Scheffels, Janne; Lund, Ingeborg
Abstract : Objectives: This study examined the perceptions of cigarette packaging and the potential impact of plain packaging regulations. The hypothesis was that the branded cigarette packages would be rated more positively than the corresponding plain packs with and without descriptors. Design: Between-subjects experimental online survey. Male and female participants were separately randomised to one of the three experimental conditions: fully branded cigarette packs, plain packs with descriptors and plain packs without descriptors; participants were asked to evaluate 12 individual cigarette packages. The participants were also asked to compare five pairs of packs from the same brand family. Setting: Norway. Participants: 1010 youths and adults aged 15–22. Primary outcome measures: Ratings of appeal, taste and harmfulness for individual packages. Ratings of taste, harm, quality, 'would rather try' and 'easier to quit' for pairs of packages. Results: Plain with and without descriptors packs were rated less positively than the branded packs on appeal (index score 1.63/1.61 vs 2.42, p<0.001), taste (index score 1.21/1.12 vs 1.70, p<0.001) and as less harmful (index score 1.0.34/0.36 vs 0.82, p<0.001) among females. Among males, the difference between the plain with and without descriptors versus branded condition was significant for appeal (index score 2.08/1.92 vs 2.58, p<0.005) and between the plain without descriptors versus branded condition for taste (index score 1.18 vs 1.70, p<0.00). The pack comparison task showed that the packs with descriptors suggesting a lower content of harmful substances, together with lighter colours, were more positively rated in the branded compared with the plain condition on dimensions less harmful (β −0.77, 95% CI −0.97 to −0.56), would rather try (β −0.32, 95% CI −0.50 to −0.14) and easier to quit (β −0.58, 95% CI −0.76 to −0.39). Conclusions: The results indicate that a shift from branded to plain cigarette packaging could lead to a reduction in positive perceptions of cigarettes among young people.